A unified jet fuel surrogate for droplet evaporation and ignition. (15th October 2016) - Chen, Xiang; Khani, E.; Chen, C.P.
Highlights: Jet fuel is modeled by a four-component surrogate fuel covering four major hydrocarbon groups. The new unified surrogate emulates real jet-A fuel distillation curve and combustion characteristics. Discrete multicomponent model is used to investigate heating, evaporation and ignition of jet-A fuel droplets. Abstract: Kerosene fuels such as Jet-A and JP-8 have been considered for dual-purposed utilizations by both jet engines and ground transportation diesel engines. These complex fuels are composed of thousands of different kinds of hydrocarbon species. The spray combustion process in diesel engines requires detailed characterization of the ignition delay of the fuels used for the preparation of stratified fuel-air charge. Ignition delay phenomenon is dominated by the fuel heating and evaporating spray processes. For computational modeling of the spray combustion processes, it is essential to have accurate characteristics of fuel thermo-physical and chemical kinetics properties. Real kerosene fuels with such a large number of components are not feasible to be used in multicomponent spray combustion calculations. The object of this study is to develop a surrogate fuel, composed of a few components, to mimic the heating, evaporating, and ignition behaviors of the real fuel. To this end, we have utilized a recently developed inversed batch distillation methodology, to select a group of hydrocarbon species that can closely match the experimental distillation curve of a Jet-A (POST-4658) blend. For chemical kinetics target, a multi-component skeleton reaction mechanism of 231 species and 5591 reactions was used to predict ignition delay times and laminar flame speeds with satisfactory results. From the hydrocarbon groups of typical kerosene fuels of linear paraffins, cycloparaffins and aromatics, we have identified the 4-component surrogate fuel as: n-dodecane/isocetane/transdecalin/toluene (mole fraction: 0.3/0.36/0.246/0.094). Droplet heating, evaporation, and ignition processes using the current unified surrogate are presented and discussed in this study.